2020
DOI: 10.1016/j.fishres.2019.105431
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating release of undersized fish through a square mesh panel in the Basque otter trawl fishery

Abstract: 17Discards of regulated species in the Basque mixed trawl fishery are a challenge. In 2006, a square mesh 18 panel (SMP) was introduced in the fishery to increase the release efficiency of undersized fish. However, 19 studies have shown that the selectivity in this fishery is based on codend selectivity and the release 20 through the SMP is inefficient due to low contact between fish and the SMP. In order to improve contact, 21we tested four different gear configurations that use different stimulators to lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Regarding SMP, the following designs were considered: (i) small SMP located at the top panel of the extension piece (SMP TS ), which is included in current regulation of the fishery; (ii) large SMP located at the top panel of the extension piece (SMP TL ); (iii) small SMP located at the bottom panel of the extension piece (SMP BS ); (iv) large SMP located at the bottom panel of the extension piece (SMP BL ) and (v) absence of SMP in the trawl. Earlier studies showed that the SMP TS performs unsatisfactorily for some species due to lack of contact between fish and the SMP TS [ 19 , 23 ]. We therefore considered different SMP designs meant to optimize the release efficiency of hake and blue whiting.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding SMP, the following designs were considered: (i) small SMP located at the top panel of the extension piece (SMP TS ), which is included in current regulation of the fishery; (ii) large SMP located at the top panel of the extension piece (SMP TL ); (iii) small SMP located at the bottom panel of the extension piece (SMP BS ); (iv) large SMP located at the bottom panel of the extension piece (SMP BL ) and (v) absence of SMP in the trawl. Earlier studies showed that the SMP TS performs unsatisfactorily for some species due to lack of contact between fish and the SMP TS [ 19 , 23 ]. We therefore considered different SMP designs meant to optimize the release efficiency of hake and blue whiting.…”
Section: Methodsmentioning
confidence: 99%
“…The second design considered was a larger SMP placed at the upper panel, potentially increasing the chance for contact with the panel. Underwater observations in earlier studies showed that hake prefer swimming close to the lower panel [ 19 , 23 , 47 ], whereas blue whiting has an erratic behavior in the SMP area, swimming quickly either towards the SMP or the codend [ 23 ]. Thus, the third and fourth designs consisted respectively of the small SMP in (i) and a larger-size panel placed at the bottom panel of the trawl.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations